CHALLENGES FOR MANAGEMENT OF LOCAL SELF-GOVERNMENT BODIES IN THE CONDITIONS OF REFORMING THE CITY BUILDING - Dovbnia , O. (Theory and Practice of Public Administration, 2020)
Legislation in the field of urban planning and architecture on the participation of bodies in the field of urban planning in the preparation and issuance of documents for urban development, including permits is considered. When reviewing this legislation, the main problems faced by customers in obtaining such documents were identified and outlined. The introduction of changes in the current legislation aimed at solving these problems, including through the creation of electronic cabinets, is analyzed. At the same time, possible risks for the implementation of these contributions were identified due to, in particular, the lack of legislative structural and functional recommendations for executive bodies of local self-government on urban planning and architecture in the regulation of urban planning. The main functions assigned to the executive bodies of local councils on urban planning and architecture in accordance with current legislation are analyzed. This analysis revealed that the legislation on certain structural units is regulated by law, but this does not apply to all executive bodies on urban planning and architecture, which may lead to delays in reform in the field of urban planning and architecture. The structures of executive bodies of local self-government on issues of urban planning and architecture of cities of regional significance are analyzed. Directions for the development of a structure for the executive bodies of local councils on urban planning and architecture are proposed. It is also proposed to group the existing units by the respective areas of activity according to the time of obtaining the expected results (for example, strategic and operational direction) for the possibility of gradual reboot by separate independent groups of the respective units in the field of urban planning and architecture.